2017
DOI: 10.1007/s11934-017-0742-3
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopy for Stone Disease in Paediatric Population is Safe and Effective in Medium-Volume and High-Volume Centres: Evidence from a Systematic Review

Abstract: Purpose of ReviewThe incidence of urinary stone disease among the paediatric population is increasing. Whilst there has been a rise in the number of original studies published on ureteroscopy (URS) in children, critical review still remains under-reported.Recent FindingsA Cochrane style systematic review was performed to identify all original articles on URS (minimum of 25 cases) for stone disease in paediatric patients between Jan. 1996 and Dec. 2016. Based on the number of reported cases, centres were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
(40 reference statements)
1
26
0
Order By: Relevance
“…A recent study by Pietropaolo et al reveals that over the past 20 years, while SWL has been the most common treatment modality, in more recent years the dissemination of URS has risen markedly [10]. Rob et al reported that there was no significant difference in the complication rates of URS (both major and minor) between medium and highvolume paediatric centres [24]. A recent meta-analysis by Geraghty et al also found the overall cost of URS procedure to be lower than SWL ($2801) compared to SWL ($3627) ($2801 vs. $3627, p = 0.03) [25].…”
Section: Role Of Swl and Pcnlmentioning
confidence: 99%
“…A recent study by Pietropaolo et al reveals that over the past 20 years, while SWL has been the most common treatment modality, in more recent years the dissemination of URS has risen markedly [10]. Rob et al reported that there was no significant difference in the complication rates of URS (both major and minor) between medium and highvolume paediatric centres [24]. A recent meta-analysis by Geraghty et al also found the overall cost of URS procedure to be lower than SWL ($2801) compared to SWL ($3627) ($2801 vs. $3627, p = 0.03) [25].…”
Section: Role Of Swl and Pcnlmentioning
confidence: 99%
“…Another study by Carry W. Jr. Herdon reported only 13.79% of the pediatric ureteric stone patients needed preoperative PUD [16].The overall failure to access rate was 2.5% in a Cochrane style systemic review [17].…”
Section: Discussionmentioning
confidence: 98%
“…However, URS for the management of ureteric stone in children is a relatively safe procedure [11]. According to the Cochrane style systemic review, the overall complication rate was 11.1% (MCCS -I = 69% and MCCS -II/III = 31%) [17].…”
Section: Discussionmentioning
confidence: 99%
“…A complication rate of 11.1% (327/2,994) was reported; 69% of these were Clavien grade I, and 31% were grade II/III. There were no Clavien grade IV and V complications (84). In another multicenter study of 642 children where semirigid ureterorenoscopy was performed for ureteric stones, a total of 54 (8.4%) complications have been documented where operative time was the only statistically significant parameter affecting the complication rate (78).…”
Section: Retrograde Intrarenal Surgerymentioning
confidence: 91%